Long-acting antibacterial polyamide fiber and preparation method thereof
By using blending reaction to establish chemical bonding in antibacterial polyamide fibers, the problem of large amount of antibacterial agent dissolution and addition of antibacterial agents is solved, long-term, stable and efficient antibacterial properties are achieved, and the preparation process is simplified.
Patent Information
- Application Number
- CN202510018365.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-06
AI Technical Summary
The existing antibacterial polyamide fibers have defects such as safety problems caused by the dissolution of antibacterial agents, difficulty in preparation and implementation, or large amount of antibacterial agents added.
The chemical bonding is established between the guanidine salt polymer antibacterial agent and the polyamide through a blending reaction to achieve the purpose of long-term antibacteriality, and the guanidine salt polymer antibacterial agent is enriched on the surface of the fiber through a simple and easy preparation method, reducing the amount of antibacterial agent added and its impact on the mechanical properties of the fiber.
The long-term, stable and efficient antibacterial properties of antibacterial fibers are achieved, while reducing the amount of antibacterial agent added, improving the mechanical properties of the fibers, and simplifying the preparation process.
Smart Images

Figure CN119800547A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional fiber materials, and specifically relates to a long-acting antibacterial polyamide fiber and a preparation method and application thereof. Background Art
[0002] Polyamide fiber or nylon fiber can be used in the manufacture of underwear, socks, sports shirts, down jackets, jackets, protective clothing, fishing nets, cord fabrics, carpets, conveyor belts, and transport belts. Since polyamide fiber itself does not have antibacterial ability, it will provide an environment for bacteria to survive and reproduce under certain conditions, threatening human health. Antibacterial components can be introduced into the fiber or the surface of the fiber through in-situ polymerization, melt spinning and surface modification to prepare antibacterial polyamide fiber, improve its comprehensive performance and expand its application. Patents CN 105386147 A, CN 105332083 A, CN 111172609 A, CN112430864 A, and CN 113062005 A respectively add Ag@mesoporous zirconium phosphate antibacterial powder, copper oxide@mesoporous zirconium phosphate gel precursor, polyamino-loaded nano zinc oxide powder, antibacterial nano metal powder wrapped with Zr(HPO4)2-loaded polyfurfuryl alcohol, and powder with negative ion release antibacterial function to the polymerization monomer, and then carry out in-situ polymerization to prepare antibacterial polyamide slices, and then melt-spin to prepare antibacterial polyamide fibers. The in-situ polymerization method is technically difficult and difficult to implement on a large scale. Patent CN 108385202 A first melt-blended long-chain carbon nylon with a silver ion-loaded antibacterial agent to prepare an antibacterial masterbatch, and then melt-spinned it with nylon slices to prepare discoloration-resistant antibacterial nylon fibers. The melt spinning method is simple and easy, but the silver ion antibacterial agent in the antibacterial fiber is antibacterial in the form of dissolution, which may have safety issues. Patent CN117587541 A first reacts hydroxyethyl hexahydrotriazine with bisphenol A diglycidyl ether to obtain an antibacterial copolymer HE, then reacts HE with a polyamide prepolymer to prepare an antibacterial polyamide, and then melt spins to obtain a long-lasting antibacterial polyamide fiber, but the amount of antibacterial agent added is large: when the amount of HE added is 30% of the mass of the prepolymer, the antibacterial rate of the antibacterial fiber prepared against Escherichia coli and Staphylococcus aureus is only 92.8% and 94.5%, respectively.
[0003] Guanidine polymer is a highly effective, broad-spectrum antibacterial agent with the advantages of good biocompatibility, low cost, non-toxicity, and good thermal stability. It has been widely used in the fields of medicine, fabrics, resins, instruments, and water treatment. Its antibacterial mechanism is to attack bacteria through the electrostatic attraction between the guanidine cationic groups it carries and the anionic groups on the surface of bacteria, causing the bacterial membrane to collapse, and the components in the bacteria to flow out, thereby inhibiting bacterial growth. However, since the guanidine group is a hydrophilic group, most guanidine polymers are highly water-soluble. If they are directly applied to the antibacterial modification of polymer materials, there are defects such as antibacterial agent dissolution and poor durability. It is necessary to chemically bond the guanidine polymer antibacterial agent to the polymer matrix through a chemical reaction, thereby giving the polymer material long-lasting antibacterial properties. Summary of the invention
[0004] In view of the safety problems caused by the dissolution of antibacterial agents, the difficulty in preparation and implementation, or the defects of large amount of antibacterial agents added in the current antibacterial polyamide fibers, the purpose of the present invention is to provide a long-lasting antibacterial polyamide fiber, which establishes a chemical bond between the guanidine salt polymer antibacterial agent and the polyamide through a blending reaction to achieve the purpose of long-lasting antibacterial.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned long-lasting antibacterial polyamide fiber, which is simple and easy to implement and can enrich the guanidine polymer antibacterial agent on the surface of the fiber. On the one hand, it can reduce the amount of antibacterial agent added and reduce costs; on the other hand, it can reduce the adverse effects of the antibacterial agent on the mechanical properties of the fiber, so that the antibacterial polyamide fiber has good mechanical properties.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A long-lasting antibacterial polyamide fiber, the long-lasting antibacterial polyamide fiber is composed of 4wt% to 20wt% of nylon-guanidine copolymer masterbatch and 80wt% to 96wt% of nylon; the nylon-guanidine copolymer masterbatch comprises a nylon-guanidine copolymer chemically bonded to a nylon and a guanidine polymer; the nylon is selected from one of nylon 6, nylon 66, and nylon 56; the nylon-guanidine copolymer is mainly composed of a structural unit shown in (structural formula A), a structural unit shown in (structural formula B), and a structural unit shown in (structural formula C),
[0008]
[0009] In the structural formula B and structural formula C, X is H or CH3 or a combination of the two;
[0010] In the structural formula B, Y is composed of the structural unit shown in (Structural Formula 1) or the structural unit shown in (Structural Formula 2) or the structural unit shown in (Structural Formula 3);
[0011] In the structural formula C, Z - Cl - Br - 、HSO4 - 、HCO3 - 、H2PO4 - 、CH3COO - or CH3(CH2) 16 COO - ;
[0012] In the structural formula C, m is a natural number of 2 to 20;
[0013] In the structural formula C, R1 is selected from the structure shown in (structural formula 4);
[0014] In the structural formula C, R is H or the structure shown in (structural formula 5) or a combination of the two.
[0015]
[0016] The present invention also provides a method for preparing the above-mentioned long-acting antibacterial polyamide fiber, which comprises the following steps:
[0017] (1) Add styrene, functional monomers, initiators, and chain transfer agents to a solvent, stir and mix them evenly, heat to 50 to 85° C., react for 9 to 12 hours, cool, dropwise add the product into ethanol or methanol to precipitate, and filter and dry to obtain polyepoxy polystyrene;
[0018] or (2) after uniformly mixing styrene, functional monomer and initiator, adding them into an aqueous solution containing a dispersant, stirring, heating to 60 to 90° C. for reaction for 7 to 11 hours, cooling, washing and drying to obtain polyepoxy polystyrene;
[0019] or (3) after styrene, functional monomer and benzoyl peroxide initiator are stirred and mixed uniformly, they are fed from the feeding port of a twin-screw extruder, reacted for 6 to 30 minutes at a temperature of 80° C. to 160° C. in zones 1 to 16 of the screw extruder, and extruded and cooled to obtain polyepoxy polystyrene;
[0020] (4) mixing the polyepoxy polystyrene prepared in step (1), step (2) or step (3) with the guanidine salt polymer in a mass ratio of 7:3 to 9:1, adding the mixture to an open mixer, a Haake internal mixer, a single screw extruder or a twin screw extruder, blending and reacting the mixture at 140 to 200° C. for 6 to 20 minutes, and cooling the mixture to obtain a polystyrene-guanidine salt copolymer functional material;
[0021] (5) mixing the polystyrene-guanidine salt copolymer functional material prepared in step (4) with nylon in a mass ratio of 3:17 to 3:7, adding the mixture to an open mixer, a Haake internal mixer, a single screw extruder or a twin screw extruder, blending and reacting for 6 to 30 minutes at 5 to 30° C. above the melting point of nylon, and cooling the mixture to obtain the nylon-guanidine salt copolymer masterbatch;
[0022] (6) After the nylon-guanidine copolymer masterbatch and nylon prepared in step (5) are fully dried, they are uniformly mixed in a mass ratio of 1:24 to 1:4, and then melt-spinned to obtain a long-lasting antibacterial polyamide fiber.
[0023] The method for preparing a long-lasting antibacterial polyamide fiber as described above, wherein the polyepoxy polystyrene is mainly composed of a structural unit shown in (Structural Formula A) and a structural unit shown in (Structural Formula D); in the structural formula D, X is H or CH3 or a combination of the two;
[0024]
[0025] The molar percentage of epoxy groups in the polyepoxy polystyrene is 3.5% to 10%; the number average molecular weight of the polyepoxy polystyrene is 3000 to 20000;
[0026] Preferably, the molar percentage of epoxy groups in the polyepoxy polystyrene is 4.5% to 8.5%; the number average molecular weight of the polyepoxy polystyrene is 4000 to 15000;
[0027] In the method for preparing the long-lasting antibacterial polyamide fiber, the guanidine polymer has a structure shown in (Structural Formula E),
[0028]
[0029] In the guanidine polymer structural formula E, Z - Cl - Br - 、HSO4 - 、HCO3 - 、H2PO4 - 、CH3COO - or CH3(CH2) 16 COO - ; m is a natural number of 2 to 20; R1 is selected from the structure shown in (Structural Formula 4); R is H or the structure shown in (Structural Formula 5) or a combination of the two;
[0030] Preferably, in the guanidine polymer structural formula E, Z - Selected from Cl - 、HCO3 -、H2PO4 - or CH3(CH2) 16 COO - ; R1 is the structure shown in (Structural Formula 6); R is the structure shown in (Structural Formula 7).
[0031]
[0032] In the method for preparing a long-lasting antibacterial polyamide fiber as described above, the functional monomer in step (1) is glycidyl methacrylate or glycidyl acrylate or a mixture of the two; the molar percentage of the functional monomer is 3.5% to 10%, preferably 5.0% to 8.0%, based on the total amount of styrene and the functional monomer;
[0033] In the method for preparing a long-lasting antibacterial polyamide fiber as described above, the total concentration of styrene and functional monomers in step (1) is 10wt% to 40wt%, preferably 20wt% to 30wt%, based on the total mass of the solvent, styrene and functional monomers;
[0034] In the method for preparing a long-lasting antibacterial polyamide fiber as described above, the initiator in step (1) is one of azobisisobutyronitrile and benzoyl peroxide; the molar percentage of the initiator is 1.0% to 3.0% based on the total amount of styrene and the functional monomer;
[0035] In the method for preparing a long-lasting antibacterial polyamide fiber as described above, the chain transfer agent in step (1) is one of dodecanethiol, mercaptoethanol, mercaptopropanol, and isopropanol; the molar percentage of the chain transfer agent is 0 to 1.2% based on the total amount of styrene and the functional monomer;
[0036] In the method for preparing the long-lasting antibacterial polyamide fiber as described above, the solvent in step (1) is one of toluene, xylene, tetrahydrofuran, and N,N-dimethylformamide.
[0037] In the method for preparing a long-lasting antibacterial polyamide fiber as described above, the functional monomer in step (2) is glycidyl methacrylate or glycidyl acrylate or a mixture of the two; the molar percentage of the functional monomer is 5.0% to 11.0%, preferably 7.0% to 10.0%, based on the total amount of styrene and the functional monomer;
[0038] In the method for preparing a long-lasting antibacterial polyamide fiber as described above, the initiator in step (2) is one of azobisisobutyronitrile and benzoyl peroxide; the molar percentage of the initiator is 1.3% to 3.8% based on the total amount of styrene and the functional monomer;
[0039] In the method for preparing a long-lasting antibacterial polyamide fiber as described above, the ratio of the mass of water to the total mass of styrene and functional monomers in step (2) is 7:1 to 10:1;
[0040] In the method for preparing a long-lasting antibacterial polyamide fiber as described above, the dispersant described in step (2) is one or a mixture of two of gelatin, polyvinyl alcohol, hydroxymethyl cellulose, hydroxyethyl cellulose, and sodium alginate; the mass percentage of the dispersant is 0.2wt% to 0.5wt% based on the mass of water.
[0041] In the method for preparing a long-lasting antibacterial polyamide fiber as described above, the functional monomer in step (3) is one of glycidyl methacrylate and glycidyl acrylate or a mixture of the two; the molar percentage of the functional monomer is 3.5% to 10%, preferably 6.0 to 9.0%, based on the total amount of styrene and the functional monomer;
[0042] In the method for preparing the long-lasting antibacterial polyamide fiber as described above, the molar percentage of the initiator in step (3) is 1.0% to 5.0% based on the total amount of styrene and the functional monomer.
[0043] In the method for preparing the long-lasting antibacterial polyamide fiber as described above, the polyepoxy polystyrene and the guanidine polymer described in step (4) are mixed in a mass ratio of 4:1 to 17:3;
[0044] In the method for preparing a long-lasting antibacterial polyamide fiber as described above, the blending reaction temperature in step (4) is 150 to 180° C.; the blending reaction time is 6 to 15 minutes;
[0045] In the method for preparing a long-lasting antibacterial polyamide fiber as described above, the polystyrene-guanidine copolymer functional material described in step (4) contains a polystyrene-guanidine copolymer; the polystyrene-guanidine copolymer is mainly composed of a structural unit shown in (Structural Formula A), a structural unit shown in (Structural Formula C) and a structural unit shown in (Structural Formula D).
[0046] In the method for preparing the long-lasting antibacterial polyamide fiber as described above, the polystyrene-guanidine salt copolymer functional material described in step (5) is mixed with the nylon in a mass ratio of 1:4 to 1:3;
[0047] In the method for preparing the long-lasting antibacterial polyamide fiber as described above, the blending reaction time in step (5) is 6 to 15 minutes.
[0048] In the method for preparing a long-lasting antibacterial polyamide fiber as described above, the nylon-guanidine salt copolymer masterbatch and nylon described in step (6) are mixed in a mass ratio of 1:24 to 1:9;
[0049] In the method for preparing a long-lasting antibacterial polyamide fiber as described above, the melt spinning described in step (6) has a temperature of 250-305°C, a spinning speed of 800-1500 m / min, a spinneret aperture of 0.2-0.5 mm, a stretching temperature of 60-120°C, and a stretching multiple of 3-4 times.
[0050] According to the method for preparing a long-lasting antibacterial polyamide fiber as described above, the antibacterial polyamide fiber described in step (6) has a breaking strength of 3.5-5.8 cN / dtex, an elongation at break of 10%-50%, an antibacterial effect on Escherichia coli, Staphylococcus aureus, and Candida albicans of more than 99.99%, and the antibacterial effect on Escherichia coli, Staphylococcus aureus, and Candida albicans can still reach more than 99% after the fiber is washed 50 times, and has good water wash resistance and high antibacterial efficiency.
[0051] According to the method for preparing a long-lasting antibacterial polyamide fiber as described above, the antibacterial polyamide fiber described in step (6) can be applied to the fields of home textile products such as clothing, protective clothing, bed sheets, socks, carpets, etc.
[0052] The above technical scheme adopted by the present invention chemically bonds the guanidine polymer antibacterial agent and the nylon molecule to the molecular chain of the styrene copolymer through a blending reaction, thereby preparing an antibacterial masterbatch containing a nylon-guanidine copolymer mainly composed of the structural unit shown in (structural formula A), the structural unit shown in (structural formula B) and the structural unit shown in (structural formula C), that is, a nylon-guanidine copolymer masterbatch; and in the fiber obtained by melt spinning the nylon-guanidine copolymer masterbatch and nylon blend, the guanidine polymer antibacterial agent is enriched on the fiber surface.
[0053] The positive beneficial effects of the present invention are:
[0054] (1) The preparation method of the antibacterial polyamide fiber provided by the present invention can enrich the antibacterial agent on the fiber surface, and the antibacterial fiber can show good antibacterial activity at a relatively low amount of antibacterial agent added;
[0055] (2) The antibacterial polyamide fiber provided by the present invention has a low content of antibacterial agent and has good mechanical properties;
[0056] (3) The antibacterial polyamide fiber provided by the present invention has a chemical bond between the antibacterial agent and the nylon matrix, and the antibacterial performance of the antibacterial fiber is long-lasting and stable, and there is no safety problem of antibacterial agent dissolution;
[0057] (4) The preparation method of the antibacterial polyamide fiber provided by the present invention is simple and easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is a scanning electron microscope image of the cross section of the antibacterial nylon 6-f9 spun fiber obtained in Example 50 of the present invention and its line scan chlorine element distribution map. DETAILED DESCRIPTION
[0059] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0060] The test standards / test methods used in the present invention are as follows:
[0061] The number average molecular weight of the polyepoxy polystyrene synthesized in Examples 1 to 20 was determined by gel permeation chromatography (GPC) using tetrahydrofuran as solvent. According to GB / T 1677-2008, the epoxy value of the polyepoxy polystyrene synthesized in Examples 1 to 20 was determined by the hydrochloric acid-acetone method, and the molar percentage of the epoxy group in the polyepoxy polystyrene was calculated in combination with the number average molecular weight determined by the GPC method.
[0062] The dispersion phenomenon in ethyl acetate (a good solvent for polystyrene) is used to determine whether the polystyrene-guanidine salt copolymer functional material prepared in Examples 21 to 45 contains a cross-linked structure: 1 g of the polystyrene-guanidine salt copolymer functional material is weighed and placed in 50 mL of ethyl acetate. After sealing, ultrasonic dispersion is performed and the dispersion phenomenon of the functional material is observed. If the polystyrene-guanidine salt copolymer functional material can be completely ultrasonically dispersed in ethyl acetate, it means that there is no cross-linked structure in the functional material.
[0063] The grafting rate of the guanidine polymer in the polystyrene-guanidine copolymer functional material prepared in Examples 21 to 45 was determined by ultraviolet spectrophotometry: a guanidine polymer aqueous solution of a series of concentrations was prepared, the absorbance of the solution at 196 nm rrm was measured, and then a standard curve was drawn; the polystyrene-guanidine copolymer functional material was ground into powder under an infrared lamp, 400 mg of the powder was accurately weighed and added to a conical flask, 200 mL of deionized water was added, and the powder was sealed and placed in a constant temperature shaking box, shaken at 25 to 40° C. for 4 h, taken out, balanced at 25° C. for 24 h, centrifuged (8000 rpm, 5 to 10 min), the supernatant was taken, diluted with deionized water to the concentration range of the standard curve, and the absorbance of the diluted solution at 196 nm was measured by an ultraviolet spectrophotometer, and the mass of the dissolved guanidine polymer was calculated according to the standard curve, thereby calculating the grafting rate of the guanidine polymer in the polystyrene-guanidine copolymer functional material.
[0064] According to GB / T 14344-2008 test method for tensile properties of chemical fiber filaments, the breaking strength and breaking elongation of the polyamide fibers spun in Examples 50 to 53 and Comparative Examples 4 to 7 were measured;
[0065] According to GB / T12490-2014 Textile Color Fastness Test for Color Fastness to Home and Commercial Washing, the antibacterial polyamide fibers spun in Examples 50 to 53 were washed:
[0066] According to GB / T20944.3-2008 Evaluation of antibacterial properties of textiles Part 3: Oscillation method, the antibacterial rates of the antibacterial polyamide fibers spun in Control Examples 5 to 7 and the antibacterial polyamide fibers spun in Examples 50 to 53 before and after washing against Escherichia coli, Staphylococcus aureus and Candida albicans were determined;
[0067] The cross-section of the antibacterial nylon 6-f9 spun fiber obtained in Example 50 broken in liquid nitrogen was observed for morphology and component scanning using a scanning electron microscope.
[0068] Examples 1 to 20 are examples of the synthesis of polyepoxy polystyrene.
[0069] Example 1: Synthesis of polyepoxy polystyrene
[0070] 83.97 g of styrene, 6.03 g of glycidyl methacrylate, 2.09 g of azobisisobutyronitrile, 0.86 g of dodecanethiol and 210 g of toluene were added in sequence into a 500 mL three-necked reaction flask equipped with a condensing reflux device, and stirred to dissolve; nitrogen was introduced into the device for 10 minutes; the temperature was raised to 75°C, and the reaction was carried out at a constant temperature for 10 hours to terminate the reaction. After the reaction solution was cooled to room temperature, it was dropped into excess ethanol, filtered, the precipitate was collected, the precipitate was washed with ethanol, and after vacuum drying at 60°C for 12 hours, a polyepoxy polystyrene product was obtained, which was recorded as SG-1.
[0071] Example 2: Synthesis of polyepoxy polystyrene
[0072] 130.19 g of styrene, 5.81 g of glycidyl acrylate, 2.13 g of azobisisobutyronitrile, 0.39 g of isopropanol and 204 g of tetrahydrofuran were added in sequence into a 500 mL three-necked reaction flask equipped with a condensing device, and stirred to dissolve; nitrogen was introduced into the device for 10 min; the temperature was raised to 50° C., and the reaction was carried out at a constant temperature for 12 h. After the reaction was terminated, the reaction solution was cooled to room temperature, and then dropped into excess methanol, filtered, and the precipitate was collected. The precipitate was washed with methanol, and vacuum dried at 60° C. for 12 h to obtain a polyepoxy polystyrene product, which was recorded as SG-2.
[0073] Example 3: Synthesis of polyepoxy polystyrene
[0074] 64.36 g of styrene, 7.64 g of glycidyl methacrylate, 4.07 g of benzoyl peroxide, 0.50 g of mercaptopropanol and 288 g of N,N-dimethylformamide were added in sequence into a 500 mL three-necked reaction flask equipped with a condensing device, and stirred to dissolve; nitrogen was introduced into the device for 10 minutes; the temperature was raised to 85°C, and the reaction was carried out at a constant temperature for 9 hours to terminate the reaction. After the reaction solution was cooled to room temperature, it was dropped into excess ethanol, filtered, the precipitated precipitate was collected, the precipitate was washed with ethanol, and after vacuum drying at 60°C for 12 hours, a polyepoxy polystyrene product was obtained, which was recorded as SG-3.
[0075] Example 4: Synthesis of polyepoxy polystyrene
[0076] 82.79 g of styrene, 7.21 g of glycidyl methacrylate, 2.05 g of benzoyl peroxide, 0.79 g of mercaptoethanol and 270 g of xylene were added in sequence into a 500 mL three-necked reaction flask equipped with a condensing device, and stirred to dissolve; nitrogen was introduced into the device for 10 min; the temperature was raised to 85° C. and the reaction was carried out at a constant temperature for 9 h. After the reaction was terminated, the reaction solution was cooled to room temperature, and then dropped into excess ethanol, filtered, and the precipitate was collected. The precipitate was washed with ethanol, and vacuum dried at 60° C. for 12 h to obtain a polyepoxy polystyrene product, which was recorded as SG-4.
[0077] Example 5: Synthesis of polyepoxy polystyrene
[0078] 31.67 g of styrene, 4.33 g of glycidyl acrylate, 1.66 g of azobisisobutyronitrile and 324 g of N,N-dimethylformamide were added in sequence into a 500 mL three-necked reaction flask equipped with a condensing device, and stirred to dissolve; nitrogen was introduced into the device for 10 min; the temperature was raised to 70°C, and the reaction was carried out at a constant temperature for 10 h. After the reaction was terminated, the reaction solution was cooled to room temperature, and then dropped into excess ethanol, filtered, and the precipitate was collected. The precipitate was washed with ethanol, and vacuum dried at 60°C for 12 h to obtain a polyepoxy polystyrene product, which was recorded as SG-5.
[0079] Example 6: Synthesis of polyepoxy polystyrene
[0080] 82.79 g of styrene, 7.21 g of glycidyl methacrylate, 2.78 g of azobisisobutyronitrile and 270 g of tetrahydrofuran were added in sequence into a 500 mL three-necked reaction flask equipped with a condensing device, and stirred to dissolve; nitrogen was introduced into the device for 10 minutes; the temperature was raised to 75°C, and the reaction was carried out at a constant temperature for 10 hours to terminate the reaction. After the reaction solution was cooled to room temperature, it was dropped into excess ethanol, filtered, and the precipitate was collected. The precipitate was washed with ethanol, and after vacuum drying at 60°C for 12 hours, a polyepoxy polystyrene material was obtained, which was recorded as SG-6.
[0081] Table 1 lists the epoxy group content and number average molecular weight data of the polyepoxy polystyrene obtained in Examples 1-6.
[0082] Table 1 Epoxy group content and number average molecular weight data of polyepoxy polystyrene synthesized by solution polymerization
[0083]
[0084] is the number average molecular weight; the amount of functional monomer is based on the total amount of functional monomer and styrene; the total monomer concentration is the total mass percentage of functional monomer and styrene, which is based on the total mass of solvent, functional monomer and styrene; the amount of initiator is based on the total amount of functional monomer and styrene; the amount of chain transfer agent is based on the total amount of functional monomer and styrene; GMA-glycidyl methacrylate; GA-glycidyl acrylate; AIBN-azobisisobutyronitrile; BPO-benzoyl peroxide; DT-dodecyl mercaptan; IPA-isopropanol; MP-mercaptopropanol; ME-mercaptoethanol; THF-tetrahydrofuran; DMF-N,N-dimethylformamide; DMB-xylene; TL-toluene
[0085] Example 7: Synthesis of polyepoxy polystyrene
[0086] 150g of 4wt% polyvinyl alcohol aqueous solution and 1050g of deionized water were added to a 2L jacketed glass reactor equipped with a serpentine condenser, and mechanically stirred (at a speed of 350rpm) for more than 5min; 159.94g of styrene monomer and 9.29g of azobisisobutyronitrile initiator were added to a 250mL beaker, stirred to completely dissolve the initiator, and then 11.49g of glycidyl methacrylate was added, stirred again to mix evenly, and then added to the reactor; after stirring for 0.5h, 75°C circulating hot water was passed into the jacket of the reactor, and the reaction was carried out at a constant temperature for 9h, cooled to room temperature, and the polymer particles were collected, and they were soaked and washed with hot water and ethanol in turn, and vacuum dried at 60°C for 12h to obtain a polyepoxy polystyrene product, recorded as SG-7.
[0087] Example 8: Synthesis of polyepoxy polystyrene
[0088] 60 g of 4 wt % gelatin aqueous solution and 1140 g of deionized water were added to a 2 L jacketed glass reactor equipped with a serpentine condenser, and mechanically stirred (at a speed of 350 rpm) for more than 5 min; 148.80 g of styrene monomer and 10.02 g of azobisisobutyronitrile initiator were added to a 250 mL beaker, stirred to completely dissolve the initiator, and then 22.63 g of glycidyl acrylate was added, stirred again to mix evenly, and then added to the reactor; after stirring for 0.5 h, 60° C. circulating hot water was passed into the jacket of the reactor, and the reaction was carried out at a constant temperature for 11 h, cooled to room temperature, and the polymer particles were collected, and they were soaked and washed with hot water and ethanol in turn, and vacuum dried at 60° C. for 12 h to obtain a polyepoxy polystyrene product, which was recorded as SG-8.
[0089] Example 9: Synthesis of polyepoxy polystyrene
[0090] 90 g of 4 wt % sodium alginate aqueous solution and 1110 g of deionized water were added to a 2 L jacketed glass reactor equipped with a serpentine condenser, and mechanically stirred (at a speed of 350 rpm) for more than 5 min; 119.18 g of styrene monomer and 6.63 g of benzoyl peroxide initiator were added to a 250 mL beaker, stirred to completely dissolve the initiator, and then 14.15 g of glycidyl methacrylate was added, stirred again to mix evenly, and then added to the reactor; after stirring for 0.5 h, 85 ° C circulating hot water was passed into the jacket of the reactor, and the reaction was carried out at a constant temperature for 8 h, cooled to room temperature, and the polymer particles were collected, and they were soaked and washed with hot water and ethanol in turn, and vacuum dried at 60 ° C for 12 h to obtain a polyepoxy polystyrene product, which was recorded as SG-9.
[0091] Example 10: Synthesis of polyepoxy polystyrene
[0092] 120g of 4wt% hydroxymethylcellulose aqueous solution and 1080g of deionized water were added to a 2L jacketed glass reactor equipped with a serpentine condenser and mechanically stirred (at a speed of 350rpm) for more than 5min; 110.38g of styrene monomer and 6.01g of benzoyl peroxide initiator were added to a 250mL beaker, stirred to completely dissolve the initiator, and then 9.62g of glycidyl methacrylate was added, stirred again to mix evenly, and then added to the reactor; after stirring for 0.5h, 90°C circulating hot water was passed into the jacket of the reactor, and the reaction was carried out at a constant temperature for 7h, cooled to room temperature, and the polymer particles were collected, and they were soaked and washed with hot water and ethanol in turn, and vacuum dried at 60°C for 12h to obtain a polyepoxy polystyrene product, recorded as SG-10.
[0093] Example 11: Synthesis of polyepoxy polystyrene
[0094] 120 g of 4 wt % hydroxyethyl cellulose aqueous solution and 1080 g of deionized water were added to a 2 L jacketed glass reactor equipped with a serpentine condenser and mechanically stirred (at a speed of 350 rpm) for more than 5 min; 151.04 g of styrene monomer and 9.94 g of azobisisobutyronitrile initiator were added to a 250 mL beaker and stirred to completely dissolve the initiator, then 20.39 g of glycidyl methacrylate was added, stirred again to mix evenly, and then added to the reactor; after stirring for 0.5 h, 70° C. circulating hot water was passed into the jacket of the reactor, and the reaction was carried out at a constant temperature for 10 h, cooled to room temperature, and the polymer particles were collected and washed with hot water and ethanol in turn, and vacuum dried at 60° C. for 12 h to obtain a polyepoxy polystyrene product, recorded as SG-11.
[0095] Example 12: Synthesis of polyepoxy polystyrene
[0096] 120g of 4wt% polyvinyl alcohol aqueous solution and 1080g of deionized water were added to a 2L jacketed glass reactor equipped with a serpentine condenser, and mechanically stirred (at a speed of 350rpm) for more than 5min; 130.25g of styrene monomer and 10.10g of benzoyl peroxide initiator were added to a 250mL beaker, stirred to completely dissolve the initiator, and then 19.75g of glycidyl methacrylate was added, stirred again to mix evenly, and then added to the reactor; after stirring for 0.5h, 80°C circulating hot water was passed into the jacket of the reactor, and the reaction was carried out at a constant temperature for 9h, cooled to room temperature, and the polymer particles were collected, and they were soaked and washed with hot water and ethanol in turn, and vacuum dried at 60°C for 12h to obtain a polyepoxy polystyrene product, recorded as SG-12.
[0097] Example 13: Synthesis of polyepoxy polystyrene
[0098] 120g of 4wt% polyvinyl alcohol aqueous solution and 1080g of deionized water were added to a 2L jacketed glass reactor equipped with a serpentine condenser, and mechanically stirred (at a speed of 350rpm) for more than 5min; 126.46g of styrene monomer and 10.03g of benzoyl peroxide initiator were added to a 250mL beaker, stirred to completely dissolve the initiator, and then 23.54g of glycidyl methacrylate was added, stirred again to mix evenly, and then added to the reactor; after stirring for 0.5h, 85°C circulating hot water was passed into the jacket of the reactor, and the reaction was carried out at a constant temperature for 9h, cooled to room temperature, and the polymer particles were collected, and they were soaked and washed with hot water and ethanol in turn, and vacuum dried at 60°C for 12h to obtain a polyepoxy polystyrene product, recorded as SG-13.
[0099] Example 14: Synthesis of polyepoxy polystyrene
[0100] 120g of 4wt% polyvinyl alcohol aqueous solution and 1080g of deionized water were added to a 2L jacketed glass reactor equipped with a serpentine condenser, and mechanically stirred (at a speed of 350rpm) for more than 5min; 136.03g of styrene monomer and 4.42g of benzoyl peroxide initiator were added to a 250mL beaker, stirred to completely dissolve the initiator, and then 13.97g of glycidyl methacrylate was added, stirred again to mix evenly, and then added to the reactor; after stirring for 0.5h, 70°C circulating hot water was passed into the jacket of the reactor, and the reaction was carried out at a constant temperature for 10h, cooled to room temperature, and the polymer particles were collected, and they were soaked and washed with hot water and ethanol in turn, and vacuum dried at 60°C for 12h to obtain a polyepoxy polystyrene product, recorded as SG-14.
[0101] Table 2 lists the epoxy group content and number average molecular weight data of the polyepoxy polystyrene obtained in Examples 7 to 14.
[0102] Table 2 Epoxy group content and number average molecular weight data of polyepoxy polystyrene synthesized by suspension polymerization
[0103]
[0104] is the number average molecular weight; the amount of functional monomer is based on the total amount of functional monomer and styrene; the water-oil ratio is the ratio of the mass of water to the total mass of styrene and functional monomer; the amount of initiator is based on the total amount of functional monomer and styrene; the amount of dispersant is based on the mass of water; GMA-glycidyl methacrylate; GA-glycidyl acrylate; AIBN-azobisisobutyronitrile; BPO-benzoyl peroxide; PVA-polyvinyl alcohol; GEL-gelatin; HMC-hydroxymethyl cellulose: HEC-hydroxyethyl cellulose; SA-sodium alginate.
[0105] Example 15: Synthesis of polyepoxy polystyrene
[0106] After dissolving 228.4 g of benzoyl peroxide in 1866.0 g of styrene, mix evenly with 134.0 g of methyl methacrylate, feed the mixture from the feeding port of a twin-screw extruder at a speed of 5 kg / h, and react and extrude at the temperatures of zones 1-16 of the screw extruder at 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, 130°C, 135°C, 135°C, 135°C, 135°C, 150°C, 150°C, and 160°C, respectively, at a rotation speed of 50 rpm. After cooling, a polyepoxy polystyrene product was obtained, which was recorded as SG-15.
[0107] Example 16: Synthesis of polyepoxy polystyrene
[0108] After dissolving 184.6 g of benzoyl peroxide in 1914.6 g of styrene, mix evenly with 85.4 g of methyl acrylate, feed the mixture from the feeding port of a twin-screw extruder at a speed of 5 kg / h, and react and extrude at the temperatures of zones 1-16 of the screw extruder at 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, 130°C, 135°C, 135°C, 135°C, 135°C, 150°C, 150°C, and 160°C, respectively, at a rotation speed of 50 rpm. After cooling, a polyepoxy polystyrene product was obtained, which was recorded as SG-16.
[0109] Example 17: Synthesis of polyepoxy polystyrene
[0110] After dissolving 135.6 g of benzoyl peroxide in 1787.8 g of styrene, mix evenly with 212.2 g of methyl methacrylate, feed the mixture from the feeding port of a twin-screw extruder at a speed of 5 kg / h, and react and extrude at the temperatures of zones 1-16 of the screw extruder at 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, 130°C, 135°C, 135°C, 135°C, 135°C, 150°C, 150°C, and 160°C, respectively, at a rotation speed of 50 rpm. After cooling, a polyepoxy polystyrene product was obtained, which was recorded as SG-17.
[0111] Example 18: Synthesis of polyepoxy polystyrene
[0112] After dissolving 91.0 g of benzoyl peroxide in 1839.7 g of styrene, mix evenly with 160.3 g of methyl methacrylate, and feed the mixture from the feeding port of a twin-screw extruder at a speed of 5 kg / h. The mixture is reacted and extruded at a speed of 50 rpm at zones 1-16 of the screw extruder at 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, 130°C, 135°C, 135°C, 135°C, 135°C, 150°C, 150°C, and 160°C. After cooling, a polyepoxy polystyrene product was obtained, which was recorded as SG-18.
[0113] Example 19: Synthesis of polyepoxy polystyrene
[0114] After dissolving 44.9 g of benzoyl peroxide in 1736.6 g of styrene, mix evenly with 263.4 g of methyl methacrylate, and feed the mixture from the feeding port of a twin-screw extruder at a speed of 5 kg / h. The mixture is reacted and extruded at a speed of 50 rpm at zones 1-16 of the screw extruder at 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, 130°C, 135°C, 135°C, 135°C, 135°C, 150°C, 150°C, and 160°C. After cooling, a polyepoxy polystyrene product was obtained, which was recorded as SG-19.
[0115] Example 20: Synthesis of polyepoxy polystyrene
[0116] After dissolving 135.1 g of benzoyl peroxide in 1762.1 g of styrene, mix evenly with 237.9 g of methyl methacrylate, feed the mixture from the feeding port of a twin-screw extruder at a speed of 5 kg / h, and react and extrude at the temperatures of zones 1-16 of the screw extruder at 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, 130°C, 135°C, 135°C, 135°C, 135°C, 150°C, 150°C, and 160°C, respectively, at a rotation speed of 50 rpm. After cooling, a polyepoxy polystyrene product was obtained, which was recorded as SG-20.
[0117] Table 3 lists the epoxy group content and number average molecular weight data of the polyepoxy polystyrene obtained in Examples 15 to 20.
[0118] Table 3 Epoxy group content and number average molecular weight data of polyepoxy polystyrene synthesized by bulk polymerization
[0119] is the number average molecular weight; the amount of functional monomer is based on the total amount of functional monomer and styrene; the amount of initiator is based on the total amount of functional monomer and styrene; GMA-glycidyl methacrylate; GA-glycidyl acrylate; BPO-benzoyl peroxide.
[0120] Four guanidine salt polymers were synthesized by melt polycondensation using dodecylamine, n-octylamine, hexamethylenediamine, pentamethylenediamine and guanidine hydrochloride as raw materials, namely, dodecylamine-terminated polyhexamethyleneguanidine hydrochloride (denoted as PHMG-L, corresponding to the structural formula (E), Z - Cl - , R1 is R is Polyhexamethyleneguanidine hydrochloride terminated with n-octylamine (denoted as PHMG-O, corresponding to the structural formula (E), Z - Cl - , R1 is R is Polyhexamethyleneguanidine hydrochloride (PHMG, corresponding to the structural formula (E), Z - Cl - , R1 is R is H), polypentamethyleneguanidine hydrochloride terminated with dodecylamine (denoted as PPMG-L, corresponding to the structural formula (E), Z - Cl - , R1 is R is It is used for the preparation of polystyrene-guanidine copolymer functional materials in Examples 21 to 45, and for the preparation of antibacterial nylon 6 masterbatch in Control Examples 1 to 3. The number average molecular weights of guanidine polymers PHMG-L, PHMG-O, PHMG, and PPMG-L were determined by matrix-assisted laser desorption ionization time-of-flight mass spectrometry, which were 731, 606, 956, and 696, respectively.
[0121] Examples 21 to 45 are examples of the preparation of polystyrene-guanidine copolymer functional materials.
[0122] Example 21: Preparation of polystyrene-guanidine salt copolymer functional material
[0123] 24 g of the polyepoxy polystyrene SG-16 prepared in Example 16 and 6 g of PHMG were put into a high-speed pulverizer and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and kneaded at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-1.
[0124] Example 22: Preparation of polystyrene-guanidine salt copolymer functional material
[0125] 24 g of the polyepoxy polystyrene SG-2 prepared in Example 2 and 6 g of PHMG were put into a high-speed pulverizer and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and kneaded at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-2.
[0126] Example 23: Preparation of polystyrene-guanidine salt copolymer functional material
[0127] 24 g of the polyepoxy polystyrene SG-10 prepared in Example 10 and 6 g of PHMG were put into a high-speed pulverizer and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and kneaded at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-3.
[0128] Example 24: Preparation of polystyrene-guanidine salt copolymer functional material
[0129] 24 g of the polyepoxy polystyrene SG-18 prepared in Example 18 and 6 g of PHMG were put into a high-speed pulverizer and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and kneaded at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-4.
[0130] Example 25: Preparation of polystyrene-guanidine salt copolymer functional material
[0131] 24 g of the polyepoxy polystyrene SG-17 prepared in Example 17 and 6 g of PHMG were put into a high-speed pulverizer and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and mixed at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-5.
[0132] Example 26: Preparation of polystyrene-guanidine salt copolymer functional material
[0133] 24 g of the polyepoxy polystyrene SG-3 prepared in Example 19 and 6 g of PHMG were put into a high-speed pulverizer and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and kneaded at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-6.
[0134] Example 27: Preparation of polystyrene-guanidine salt copolymer functional material
[0135] 24 g of the polyepoxy polystyrene SG-8 prepared in Example 8 and 6 g of PHMG were put into a high-speed pulverizer and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and kneaded at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-7.
[0136] Example 28: Preparation of polystyrene-guanidine salt copolymer functional material
[0137] 24 g of the polyepoxy polystyrene SG-13 prepared in Example 13 and 6 g of PHMG were put into a high-speed pulverizer and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and kneaded at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-8.
[0138] Example 29: Preparation of polystyrene-guanidine salt copolymer functional material
[0139] 24 g of the polyepoxy polystyrene SG-14 prepared in Example 14 and 6 g of PHMG were put into a high-speed pulverizer and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and kneaded at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-9.
[0140] From the data of Examples 21 to 27 in Table 4, it can be seen that as the epoxy group content of the polyepoxy polystyrene increases, the grafting rate of the guanidine polymer of the polystyrene-guanidine copolymer functional material continues to increase. From the data of Examples 28 and 29 in Table 4, it can be seen that when the epoxy group content of the polyepoxy polystyrene is too large or the relative molecular mass is too large, a large number of cross-linked structures will be generated during the mixing and blending process.
[0141] Table 4: Guanidine polymer grafting rate data of polystyrene-guanidine copolymer functional materials prepared in Examples 21-29 and their dispersion in ethyl acetate
[0142]
[0143] Example 30: Preparation of polystyrene-guanidine salt copolymer functional material
[0144] 25.5 g of the polyepoxy polystyrene SG-6 prepared in Example 6 and 4.5 g of PHMG-L were put into a high-speed pulverizer and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and kneaded at 150° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-10.
[0145] Example 31: Preparation of polystyrene-guanidine salt copolymer functional material
[0146] 25.5 g of the polyepoxy polystyrene SG-6 prepared in Example 6 and 4.5 g of PHMG-L were put into a high-speed pulverizer and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and kneaded at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-11.
[0147] Example 32: Preparation of polystyrene-guanidine salt copolymer functional material
[0148] 25.5 g of the polyepoxy polystyrene SG-6 prepared in Example 6 and 4.5 g of PHMG-L were put into a high-speed grinder and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and mixed at 180° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-12.
[0149] Example 33: Preparation of polystyrene-guanidine salt copolymer functional material
[0150] 25.5 g of the polyepoxy polystyrene SG-6 prepared in Example 6 and 4.5 g of PHMG-L were put into a high-speed pulverizer and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and kneaded at 190° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-13.
[0151] Example 34: Preparation of polystyrene-guanidine salt copolymer functional material
[0152] 25.5 g of the polyepoxy polystyrene SG-6 prepared in Example 6 and 4.5 g of PHMG-L were put into a high-speed grinder and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and mixed at 200° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-14.
[0153] Example 35: Preparation of polystyrene-guanidine salt copolymer functional material
[0154] 25.5 g of the polyepoxy polystyrene SG-6 prepared in Example 6 and 4.5 g of PHMG-L were put into a high-speed grinder and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and mixed at 210° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-15.
[0155] Example 36: Preparation of polystyrene-guanidine salt copolymer functional material
[0156] 25.5 g of the polyepoxy polystyrene SG-6 prepared in Example 6 and 4.5 g of PPMG-L were put into a high-speed pulverizer and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and kneaded at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-16.
[0157] Table 5: Guanidine polymer grafting rate data of polystyrene-guanidine copolymer functional materials prepared in Examples 30-36 and their dispersion in ethyl acetate
[0158]
[0159] From the data of Examples 30 to 35 in Table 5, it can be seen that with the increase of the banburying temperature, the grafting rate of the guanidine polymer of the polystyrene-guanidine copolymer functional material continues to decrease: when the banburying temperature reaches 210°C, a large number of cross-linked structures exist in the banburying product.
[0160] Example 37: Preparation of polystyrene-guanidine salt copolymer functional material
[0161] 27 g of the polyepoxy polystyrene SG-9 prepared in Example 9 and 3 g of PHMG-O were put into a high-speed grinder and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and mixed at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-17.
[0162] Example 38: Preparation of polystyrene-guanidine salt copolymer functional material
[0163] 25.5 g of the polyepoxy polystyrene SG-9 prepared in Example 9 and 4.5 g of PHMG-O were put into a high-speed pulverizer and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and kneaded at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-18.
[0164] Example 39: Preparation of polystyrene-guanidine salt copolymer functional material
[0165] 24.9 g of the polyepoxy polystyrene SG-9 prepared in Example 9 and 5.1 g of PHMG-O were put into a high-speed grinder and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and mixed at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-19.
[0166] Example 40: Preparation of polystyrene-guanidine salt copolymer functional material
[0167] 24.6 g of the polyepoxy polystyrene SG-9 prepared in Example 9 and 5.4 g of PHMG-O were put into a high-speed grinder and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and kneaded at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-20.
[0168] Example 41: Preparation of polystyrene-guanidine salt copolymer functional material
[0169] 24 g of the polyepoxy polystyrene SG-9 prepared in Example 9 and 6 g of PHMG-O were put into a high-speed grinder and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and mixed at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-21.
[0170] Example 42: Preparation of polystyrene-guanidine salt copolymer functional material
[0171] 22.5 g of the polyepoxy polystyrene SG-9 prepared in Example 9 and 7.5 g of PHMG-O were put into a high-speed pulverizer and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and kneaded at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-22.
[0172] Example 43: Preparation of polystyrene-guanidine salt copolymer functional material
[0173] 21 g of the polyepoxy polystyrene SG-9 prepared in Example 9 and 9 g of PHMG-O were put into a high-speed grinder and crushed for 30 seconds to obtain a uniformly mixed powder, which was then added to an internal mixer and kneaded at 170° C. and 60 rpm for 8 minutes. After cooling, a polystyrene-guanidine copolymer functional material was obtained, which was recorded as PSGP-23.
[0174] From the data of Examples 37 to 43 in Table 6, it can be seen that as the amount of guanidine polymer used increases, the grafting rate of the guanidine polymer of the polystyrene-guanidine copolymer functional material decreases continuously.
[0175] Table 6: Guanidine polymer grafting rate data of polystyrene-guanidine copolymer functional materials prepared in Examples 37-43 and their dispersion in ethyl acetate
[0176]
[0177] Example 44: Preparation of polystyrene-guanidine salt copolymer functional material
[0178] 664g of polyepoxy polystyrene SG-9 prepared under the conditions of Example 9 and 136g of PHMG-O were put into a high-speed pulverizer and crushed for 30s to obtain a uniformly mixed powder; the powder was added to the feeding hopper of a twin-screw extruder, and the mixture was mixed and reacted and extruded at a feeding speed of 2rpm, screw zone 1, zone 2, zone 3, zone 4, zone 5 and die head temperatures of 120°C, 170°C, 170°C, 170°C, 170°C and 160°C, respectively, and a screw speed of 100rpm. After cooling, a polystyrene-guanidine salt copolymer functional material was obtained, which was recorded as PSGP-24. PSGP-24 can be completely dispersed in ethyl acetate, and the grafting rate of its guanidine salt polymer is 95.35%.
[0179] Example 45: Preparation of polystyrene-guanidine salt copolymer functional material
[0180] 664g of the polyepoxy polystyrene SG-11 prepared in Example 11 and 136g of PHMG were put into a high-speed pulverizer and crushed for 30s to obtain a uniformly mixed powder; the powder was added to the feeding hopper of a twin-screw extruder, and the blending reaction was extruded under the conditions of a feeding speed of 2rpm, screw zone 1, zone 2, zone 3, zone 4, zone 5 and die head temperatures of 120°C, 170°C, 170°C, 170°C, 170°C and 160°C, respectively, and a screw speed of 100rpm. After cooling, a polystyrene-guanidine salt copolymer functional material was obtained, which was recorded as PSGP-25. PSGP-25 can be completely dispersed in ethyl acetate, and the grafting rate of its guanidine salt polymer is 96.64%.
[0181] Example 46: Preparation of nylon-guanidine copolymer masterbatch
[0182] The polystyrene-guanidine copolymer functional material PSGP-24 prepared in Example 44 was vacuum dried at 80°C for 24 h, and mixed evenly with nylon 6 chips vacuum dried at 120°C for 48 h in a mass ratio of 1:4, and then added to the feeding hopper of a twin-screw extruder. The blending reaction was extruded at a feeding speed of 3 rpm, screw zone 1, zone 2, zone 3, zone 4, zone 5 and head temperatures of 190°C, 245°C, 245°C, 245°C, 245°C and 235°C respectively, and a screw speed of 100 rpm. After cooling, the mixture was pelletized and dried to obtain a nylon-guanidine copolymer masterbatch 1 with a guanidine polymer content of 3.4 wt%.
[0183] Example 47: Preparation of nylon-guanidine copolymer masterbatch
[0184] The polystyrene-guanidine copolymer functional material PSGP-25 prepared in Example 45 was vacuum dried at 80°C for 24 h, and mixed evenly with nylon 6 chips vacuum dried at 120°C for 48 h in a mass ratio of 1:4, and then added to the feeding hopper of a twin-screw extruder. The blending reaction was extruded at a feeding speed of 3 rpm, the temperatures of screw zones 1, 2, 3, 4, 5 and the die head were 190°C, 245°C, 245°C, 245°C, 245°C and 235°C respectively, and the screw speed was 100 rpm. After cooling, the mixture was pelletized and dried to obtain a nylon-guanidine copolymer masterbatch 2 with a guanidine polymer content of 3.4 wt%.
[0185] Example 48: Preparation of nylon-guanidine copolymer masterbatch
[0186] The polystyrene-guanidine copolymer functional material PSGP-24 prepared in Example 44 was vacuum dried at 80°C for 24 h, and mixed evenly with nylon 66 chips vacuum dried at 120°C for 48 h in a mass ratio of 1:4, and then added to the feeding hopper of a twin-screw extruder. The blending reaction was extruded at a feeding speed of 3 rpm, the temperatures of screw zones 1, 2, 3, 4, 5 and the die head were 240°C, 270°C, 270°C, 270°C, 270°C and 255°C respectively, and the screw speed was 100 rpm. After cooling, the mixture was pelletized and dried to obtain a nylon-guanidine copolymer masterbatch 3 with a guanidine polymer content of 3.4 wt%.
[0187] Example 49: Preparation of nylon-guanidine copolymer masterbatch
[0188] The polystyrene-guanidine copolymer functional material PSGP-24 prepared in Example 44 was vacuum dried at 80°C for 24 h, and mixed evenly with nylon 56 chips vacuum dried at 120°C for 48 h in a mass ratio of 1:3, and then added to the feeding hopper of a twin-screw extruder. The blending reaction was extruded at a feeding speed of 3 rpm, the temperatures of screw zones 1, 2, 3, 4, 5 and the die head were 240°C, 270°C, 270°C, 270°C, 270°C and 260°C respectively, and the screw speed was 100 rpm. After cooling, the mixture was pelletized and dried to obtain a nylon-guanidine copolymer masterbatch 4 with a guanidine polymer content of 4.25 wt%.
[0189] Comparative Example 1: Preparation of Antibacterial Nylon 6 Masterbatch
[0190] 48 g of PHMG and 752 g of nylon 6 slices dried in vacuum at 120° C. for 48 h were put into a high-speed pulverizer for pulverization and mixing for 30 seconds, and then added to the feeding hopper of a twin-screw extruder. The mixture was blended and extruded at a feeding speed of 3 rpm, screw zone 1, zone 2, zone 3, zone 4, zone 5 and die head temperatures of 215° C., 245° C., 245° C., 245° C., 235° C., respectively, and a screw speed of 100 rpm. After cooling, the mixture was pelletized and dried to obtain an antibacterial nylon 6 masterbatch 1 with a guanidine polymer content of 6 wt%.
[0191] Comparative Example 2: Preparation of Antibacterial Nylon 6 Masterbatch
[0192] 48 g of PHMG-O and 752 g of nylon 6 slices dried in vacuum at 120° C. for 48 h were put into a high-speed grinder and crushed and mixed for 30 seconds. Then, the mixture was added to the feeding hopper of a twin-screw extruder and blended and extruded at a feeding speed of 3 rpm, screw zone 1, zone 2, zone 3, zone 4, zone 5 and die head temperatures of 215° C., 245° C., 245° C., 245° C., 235° C., respectively, and a screw speed of 100 rpm. After cooling, the mixture was pelletized and dried to obtain an antibacterial nylon 6 masterbatch 2 with a guanidine polymer content of 6 wt%.
[0193] Comparative Example 3: Preparation of Antibacterial Nylon 6 Masterbatch
[0194] 27.2 g of PHMG-O, 80 g of the polyepoxy polystyrene SG-9 prepared in Example 9 and 692.8 g of nylon 6 chips dried in vacuum at 120° C. for 48 h were put into a high-speed grinder and crushed and mixed for 30 seconds. Then, they were added to the feeding hopper of a twin-screw extruder. The mixture was mixed and reacted and extruded at a feeding speed of 3 rpm, the temperatures of screw zones 1, 2, 3, 4, 5 and the die head of 190° C., 240° C., 240° C., 240° C., 240° C. and 235° C., respectively, and the screw speed of 100 rpm. After cooling, the mixture was pelletized and dried to obtain an antibacterial nylon 6 masterbatch 3 with a guanidine polymer content of 3.4 wt%.
[0195] Comparative Example 4: Preparation of nylon 6 fiber
[0196] The nylon 6 slices were vacuum dried at 120℃ for 48h, added to the feeding hopper of the spinning machine, and melt-spinning was performed using a spinneret with 36 holes and an aperture of 0.3mm. The pre-oriented yarn was obtained under the conditions of screw 1-4 zone temperature, flange temperature, elbow temperature and box temperature of 255-265℃ and winding speed of 800m / min. The pre-oriented yarn was heat-stretched at the maximum stretchable multiple using a parallel drawing machine at a hot plate temperature of 60℃ and a hot plate temperature of 120℃ to obtain nylon 6 fiber, which was recorded as nylon 6-f0.
[0197] Comparative Example 5: Preparation of antibacterial nylon 6 fiber
[0198] The antibacterial nylon 6 masterbatch 1 and nylon 6 chips prepared in control example 1 were vacuum dried at 120°C for 48h, then mixed in a certain proportion to prepare blended chips with guanidine polymer content of 1.5% and 2.0%, and added to the feeding hopper of the spinning machine in turn, and melt spinning was carried out using a spinneret with 36 holes and an aperture of 0.3mm. Under the conditions of screw 1-4 zone temperature, flange temperature, elbow temperature and box temperature of 252-262°C and a winding speed of 800m / min, pre-oriented yarns were obtained. Using a parallel drawing machine, under the conditions of a hot plate temperature of 60°C and a hot plate temperature of 120°C, the pre-oriented yarns were hot-drawn at the maximum stretchable multiple to obtain a series of nylon 6 fibers, which were recorded as antibacterial nylon 6-f1 and antibacterial nylon 6-f2.
[0199] Comparative Example 6: Preparation of antibacterial nylon 6 fiber
[0200] The antibacterial nylon 6 masterbatch 2 and nylon 6 chips prepared in control example 2 were vacuum dried at 120°C for 48h, then mixed in a certain proportion to prepare a blended chip with a guanidine polymer content of 1.0%, added to the feeding hopper of the spinning machine, and melt-spinning was performed using a spinneret with 36 holes and an aperture of 0.3mm. Under the conditions of screw 1-4 zone temperature, flange temperature, elbow temperature and box temperature of 255-262°C and a winding speed of 800m / min, a pre-oriented yarn was obtained. Using a parallel drawing machine, under the conditions of a hot plate temperature of 60°C and a hot plate temperature of 120°C, the pre-oriented yarn was hot-drawn at the maximum stretchable multiple to obtain nylon 6 fiber, which was recorded as antibacterial nylon 6-f3.
[0201] Comparative Example 7: Preparation of antibacterial nylon 6 fiber
[0202] The antibacterial nylon 6 masterbatch 3 and nylon 6 chips prepared in control example 3 were vacuum dried at 120°C for 48h, then mixed in a certain proportion to prepare a blended chip with a guanidine polymer content of 1.0%, added to the feeding hopper of the spinning machine, and melt-spinning was performed using a spinneret with 36 holes and a pore size of 0.3mm. Under the conditions of screw 1-4 zone temperature, flange temperature, elbow temperature and box temperature of 255-262°C and a winding speed of 800m / min, a pre-oriented yarn was obtained. Using a parallel drawing machine, under the conditions of a hot plate temperature of 60°C and a hot plate temperature of 120°C, the pre-oriented yarn was hot-drawn at the maximum stretchable multiple to obtain nylon 6 fiber, which was recorded as antibacterial nylon 6-f4.
[0203] Example 50: Preparation of antibacterial nylon 6 fiber
[0204] The nylon-guanidine copolymer masterbatch 1 and nylon 6 chips prepared in Example 46 were vacuum dried at 120°C for 48h, and then mixed in a certain proportion to prepare a series of blended chips with guanidine polymer contents of 0.21%, 0.27%, 0.33%, 0.39%, and 0.57%, which were added to the feeding hopper of the spinning machine in sequence, and melt spinning was performed using a spinneret with 36 holes and an aperture of 0.3mm. Under the conditions of screw 1-4 zone temperature, flange temperature, elbow temperature and box temperature of 250-260°C and a winding speed of 800m / min, pre-oriented yarns were obtained. A parallel drawing machine was used to heat-draw the pre-oriented yarn to the maximum stretchable multiple under the conditions of a hot plate temperature of 60°C and a hot plate temperature of 120°C to produce a series of nylon 6 fibers, which were named antibacterial nylon 6-f5, antibacterial nylon 6-f6, antibacterial nylon 6-f7, antibacterial nylon 6-f8 and antibacterial nylon 6-f9.
[0205] Example 51: Preparation of antibacterial nylon 6 fiber
[0206] The nylon-guanidine copolymer masterbatch 2 and nylon 6 chips prepared in Example 47 were vacuum dried at 120°C for 48h, and then mixed in a certain proportion to prepare blended chips with guanidine polymer contents of 0.21%, 0.27%, 0.33%, and 0.39%, which were added to the feeding hopper of the spinning machine in sequence, and melt spinning was performed using a spinneret with 36 holes and an aperture of 0.3mm. Under the conditions of screw 1-4 zone temperature, flange temperature, elbow temperature, and box temperature of 250-260°C and a winding speed of 800m / min, pre-oriented yarns were obtained. A parallel drawing machine was used to heat-draw the pre-oriented yarn to the maximum stretchable multiple under the conditions of a hot plate temperature of 60°C and a hot plate temperature of 120°C to produce a series of nylon 6 fibers, which were named antibacterial nylon 6-f10, antibacterial nylon 6-f11, antibacterial nylon 6-f12 and antibacterial nylon 6-f13.
[0207] Example 52: Preparation of antibacterial nylon 66 fiber
[0208] The nylon-guanidine copolymer masterbatch 3 prepared in Example 48 and the nylon 66 chips were vacuum dried at 120°C for 48 hours, and then mixed in a certain proportion to prepare a series of blended chips; pure nylon 66 chips, blended chips with 0.33% and 0.39% guanidine polymer content were added to the feeding hopper of the spinning machine in turn, and melt spinning was carried out using a spinneret with 36 holes and a pore size of 0.3mm. Under the conditions of screw 1-4 zone temperature, flange temperature, elbow temperature and box temperature of 290-305°C and a winding speed of 800m / min, pre-oriented yarns were obtained. Using a parallel drawing machine, under the conditions of a hot plate temperature of 60°C and a hot plate temperature of 120°C, the pre-oriented yarns were heat-drawn at the maximum stretchable multiple to obtain a series of nylon 66 fibers, which were respectively recorded as nylon 66-f0, antibacterial nylon 66-f1 and antibacterial nylon 66-f2.
[0209] Example 53: Preparation of antibacterial nylon 56 fiber
[0210] The nylon-guanidine copolymer masterbatch 4 prepared in Example 49 and the nylon 56 chips were vacuum dried at 120°C for 48 hours, and then mixed in a certain proportion to prepare a series of blended chips; pure nylon 56 chips, blended chips with 0.33% and 0.39% guanidine polymer content were added to the feeding hopper of the spinning machine in sequence, and melt spinning was carried out using a spinneret with 36 holes and an aperture of 0.3mm. Under the conditions of screw 1-4 zone temperature, flange temperature, elbow temperature and box temperature of 270-285°C and a winding speed of 800m / min, pre-oriented yarns were obtained. Using a parallel drawing machine, under the conditions of a hot plate temperature of 60°C and a hot plate temperature of 120°C, the pre-oriented yarns were heat-drawn at the maximum stretchable multiple to obtain a series of nylon 56 fibers, which were recorded as nylon 56-f0, antibacterial nylon 56-f1 and antibacterial nylon 56-f2.
[0211] Table 7 Mechanical properties and antibacterial properties of antibacterial polyamide fibers
[0212]
[0213] From the data of antibacterial nylon 6-f1 and antibacterial nylon 6-f2 spun from comparative example 5 in Table 7, it can be seen that when the antibacterial nylon 6 masterbatch 1 prepared from comparative example 1 (i.e., melt blending of PHMG and nylon 6) is used to spin antibacterial nylon 6 fibers, the fibers only show excellent antibacterial properties when the content of the guanidine polymer reaches 2.0wt%. Compared with pure nylon 6 fibers (nylon 6-f0), the maximum stretchable multiple and mechanical properties are significantly reduced.
[0214] From the data of antibacterial nylon 6-f3 spun by comparative example 6 in Table 7, it can be seen that when the antibacterial nylon 6 masterbatch 2 prepared by comparative example 2 (i.e., melt blending of PHMG-O and nylon 6) is used to spin antibacterial fibers, when the content of guanidine polymer reaches 1.0wt%, the fibers show good antibacterial properties. Compared with the antibacterial nylon 6 masterbatch 1 prepared by directly blending PHMG and nylon 6, the amount of guanidine polymer required to be added for spinning antibacterial nylon 6 fibers decreases, and accordingly, the maximum tensile multiple and mechanical properties of the antibacterial fibers are significantly increased, but compared with the blank nylon 6 fibers, there is still a significant decrease.
[0215] From the data of the antibacterial nylon 6-f4 spun by control example 7 in Table 7, it can be seen that when the antibacterial nylon 6 masterbatch 3 prepared by control example 3 (i.e., one-step melt blending of 3.4wt% PHMG-O, 10wt% polyepoxy styrene copolymer and 86.6wt% nylon 6) is used to spin antibacterial fibers, similar to the antibacterial nylon 6 masterbatch 2 prepared by directly blending PHMG-O and nylon 6. Only when the content of guanidine polymer reaches 1.0wt%, the fiber exhibits better antibacterial properties; the mechanical properties of the fiber are slightly improved, but there is still a large gap with the mechanical properties of the blank nylon 6 fiber.
[0216] From the data of the antibacterial nylon 6 fibers (antibacterial nylon 6-f5-antibacterial nylon 6-f13) spun in Example 50 and Example 51, the antibacterial nylon 66 fibers (antibacterial nylon 66-f1 and antibacterial nylon 66-f2) spun in Example 52, and the antibacterial nylon 56 fibers (antibacterial nylon 56-f1 and antibacterial nylon 56-f2) spun in Example 53 in Table 7, it can be seen that when the nylon-guanidine copolymer masterbatch of the present invention is used to spin antibacterial nylon 6 fibers, antibacterial nylon 66 fibers and antibacterial nylon 56 fibers, when the content of guanidine polymer reaches 0.27wt%, the fibers show excellent antibacterial properties, and the breaking strength of the obtained antibacterial fibers is only slightly reduced relative to that of pure nylon fibers.
[0217] It can be seen that the antibacterial masterbatch prepared by direct melt blending of guanidine polymer and nylon, and the antibacterial masterbatch prepared by one-step melt blending of guanidine polymer, polyepoxy polystyrene and nylon, compared with the nylon-guanidine copolymer masterbatch prepared by two-step melt blending (first melt blending of guanidine polymer and polyepoxy polystyrene to prepare polystyrene-guanidine copolymer functional material, and then melt blending the functional material with nylon), only requires a small amount of guanidine polymer to exhibit excellent antibacterial properties when preparing antibacterial nylon fibers, and the resulting antibacterial fibers also have excellent mechanical properties.
[0218] Figure 1The antibacterial nylon 6-f9 primary fiber is spun by using the nylon-guanidine copolymer masterbatch of the present invention. After being brittlely fractured in liquid nitrogen, a scanning electron microscope image of the cross section and a Cl element distribution curve obtained by performing a Cl element line scan along the radial direction from the center of the fiber show that the Cl element content gradually increases from the center of the fiber to the surface of the fiber, especially on the surface of the fiber, the Cl element content increases significantly, indicating that the nylon-guanidine copolymer masterbatch prepared by the present invention is applied to spinning antibacterial fibers from a nylon system, and the guanidine polymer is enriched on the surface of the antibacterial fiber, so that it can exert excellent antibacterial properties at a very low addition amount.
[0219] Table 8 Antibacterial properties of antibacterial polyamide fibers washed 10 times and 50 times
[0220]
[0221] It can be seen from Table 8 that the antibacterial polyamide fiber prepared by the nylon-guanidine copolymer masterbatch prepared by the two-step melt blending of the present invention has good water washing resistance and still has excellent antibacterial performance after 50 times of water washing.
[0222] Although the present disclosure has been disclosed above through the description of the specific embodiments of the present disclosure, it should be understood that those skilled in the art can design various modifications, improvements or equivalents to the present disclosure within the spirit and scope of the attached scheme. These modifications, improvements or equivalents should also be considered to be included in the scope of protection claimed by the present disclosure.
Claims
1. A long-lasting antibacterial polyamide fiber, characterized in that: The long-lasting antibacterial polyamide fiber is composed of 4wt% to 20wt% of nylon-guanidine copolymer masterbatch and 80wt% to 96wt% of nylon; the nylon-guanidine copolymer masterbatch comprises a nylon-guanidine copolymer chemically bonded to a nylon and a guanidine polymer; the nylon is selected from one of nylon 6, nylon 66, and nylon 56; the nylon-guanidine copolymer is mainly composed of a structural unit shown in (Structural Formula A), a structural unit shown in (Structural Formula B), and a structural unit shown in (Structural Formula C), In the structural formula B and structural formula C, X is H or CH3 or a combination of the two; In the structural formula B, Y is composed of the structural unit represented by (Structural Formula 1) or the structural unit represented by (Structural Formula 2) or the structural unit represented by (Structural Formula 3); In the structural formula C, Z - Cl - Br - 、HSO4 - 、HCO3 - 、H2PO4 - 、CH3COO - or CH3(CH2) 16 COO - ; In the structural formula C, m is a natural number of 2 to 20; In the structural formula C, R1 is selected from the structure shown in (structural formula 4); In the structural formula C, R is H or the structure shown in (structural formula 5) or a combination of the two.
2. A method for preparing a long-lasting antibacterial polyamide fiber as claimed in claim 1, characterized in that: The preparation method comprises the following steps: (1) adding styrene, functional monomers, initiators and chain transfer agents into a solvent, stirring and mixing them uniformly, heating to 50 to 85° C. to react for 9 to 12 hours, cooling and dropping the product into ethanol or methanol to precipitate, filtering and drying to obtain polyepoxy polystyrene; or (2) after uniformly mixing styrene, functional monomer and initiator, adding them into an aqueous solution containing a dispersant, stirring, heating to 60 to 90° C. for reaction for 7 to 11 hours, cooling, washing and drying to obtain polyepoxy polystyrene; or (3) after styrene, functional monomer and benzoyl peroxide initiator are stirred and mixed uniformly, they are fed from the feeding port of a twin-screw extruder, reacted for 6 to 30 minutes at a temperature of 80° C. to 160° C. in zones 1 to 16 of the screw extruder, and extruded and cooled to obtain polyepoxy polystyrene; (4) mixing the polyepoxy polystyrene prepared in step (1), step (2) or step (3) with the guanidine salt polymer in a mass ratio of 7:3 to 9:1, adding the mixture to an open mixer, a Haake internal mixer, a single screw extruder or a twin screw extruder, blending and reacting the mixture at 140 to 200° C. for 6 to 20 minutes, and cooling the mixture to obtain a polystyrene-guanidine salt copolymer functional material; (5) mixing the polystyrene-guanidine salt copolymer functional material prepared in step (4) with nylon in a mass ratio of 3:17 to 3:7, adding the mixture to an open mixer, a Haake internal mixer, a single screw extruder or a twin screw extruder, blending and reacting for 6 to 30 minutes at 5 to 30° C. above the melting point of nylon, and cooling the mixture to obtain the nylon-guanidine salt copolymer masterbatch; (6) After the nylon-guanidine copolymer masterbatch and nylon prepared in step (5) are fully dried, they are uniformly mixed in a mass ratio of 1:24 to 1:4, and then melt-spinned to obtain a long-lasting antibacterial polyamide fiber.
3. The method for preparing a long-lasting antibacterial polyamide fiber according to claim 2, characterized in that: The polyepoxy polystyrene is mainly composed of the structural unit shown in (Structural Formula A) and the structural unit shown in (Structural Formula D): In the structural formula D, X is H or CH3 or a combination of the two; The molar percentage of epoxy groups in the polyepoxy polystyrene is 3.5% to 10%; the number average molecular weight of the polyepoxy polystyrene is 3000 to 20000; Preferably, the molar percentage of epoxy groups in the polyepoxy polystyrene is 4.5% to 8.5%; the number average molecular weight of the polyepoxy polystyrene is 4000 to 15000; The guanidine polymer has a structure shown in (Structural Formula E), In the guanidine polymer structural formula E, Z - Cl - Br - 、HSO4 - 、HCO3 - 、H2PO4 - 、CH3COO - or CH3(CH2) 16 COO - ; m is a natural number of 2 to 20; R1 is selected from the structure shown in (Structural Formula 4); R is H or the structure shown in (Structural Formula 5) or a combination of the two; Preferably, in the guanidine polymer structural formula E, Z - Selected from Cl - 、HCO3 - 、H2PO4 - or CH3(CH2) 16 COO - ; R1 is the structure shown in (Structural Formula 6); R is the structure shown in (Structural Formula 7).
4. The method for preparing a long-lasting antibacterial polyamide fiber according to claim 2, characterized in that: In step (1), the functional monomer is glycidyl methacrylate or glycidyl acrylate or a mixture of the two; the molar percentage of the functional monomer is 3.5% to 10.0%, preferably 5.0% to 8.0%, based on the total amount of styrene and the functional monomer; The total concentration of styrene and functional monomers is 10wt% to 40wt% based on the total mass of the solvent, styrene and functional monomers, preferably 20wt% to 30wt%; The initiator is azobisisobutyronitrile or benzoyl peroxide; the molar percentage of the initiator is 1.0% to 3.0% based on the total amount of styrene and functional monomers; The chain transfer agent is one of dodecanethiol, mercaptoethanol, mercaptopropanol and isopropanol; the molar percentage of the chain transfer agent is 0 to 1.2% based on the total amount of styrene and the functional monomer; The solvent is one of toluene, xylene, tetrahydrofuran and N,N-dimethylformamide.
5. The method for preparing a long-lasting antibacterial polyamide fiber according to claim 2, characterized in that: In step (2), the functional monomer is glycidyl methacrylate or glycidyl acrylate or a mixture of the two; the molar percentage of the functional monomer is 5.0% to 11.0%, preferably 7.0% to 10.0%, based on the total amount of styrene and the functional monomer; The initiator is azobisisobutyronitrile or benzoyl peroxide; the molar percentage of the initiator is 1.3% to 3.8% based on the total amount of styrene and functional monomers; The ratio of the mass of water to the total mass of styrene and functional monomers is 7:1 to 10:1; The dispersant is one or a mixture of gelatin, polyvinyl alcohol, hydroxymethyl cellulose, hydroxyethyl cellulose, sodium alginate; the mass percentage of the dispersant is 0.2wt% to 0.5wt% based on the mass of water.
6. The method for preparing a long-lasting antibacterial polyamide fiber according to claim 2, characterized in that: In step (3), the functional monomer is glycidyl methacrylate or glycidyl acrylate or a mixture of the two; the molar percentage of the functional monomer is 3.5% to 10%, preferably 6.0 to 9.0%, based on the total amount of styrene and the functional monomer; the molar percentage of the initiator is 1.0% to 5.0%, based on the total amount of styrene and the functional monomer.
7. The method for preparing a long-lasting antibacterial polyamide fiber according to claim 2, characterized in that: In step (4), the polyepoxy polystyrene and the guanidine polymer are mixed in a mass ratio of 4:1 to 17:3; the blending reaction temperature is 150 to 180°C; the blending reaction time is 6 to 15 minutes; the polystyrene-guanidine copolymer functional material contains a polystyrene-guanidine copolymer; the polystyrene-guanidine copolymer is mainly composed of the structural unit shown in (Structural Formula A), the structural unit shown in (Structural Formula C) and the structural unit shown in (Structural Formula D).
8. The method for preparing a long-lasting antibacterial polyamide fiber according to claim 2, characterized in that: In step (5), the polystyrene-guanidine salt copolymer functional material and the nylon are mixed in a mass ratio of 1:4 to 1:3; and the blending reaction time is 6 to 15 minutes.
9. The method for preparing a long-lasting antibacterial polyamide fiber according to claim 2, characterized in that: In step (6), the nylon-guanidine copolymer masterbatch is mixed with the nylon in a mass ratio of 1:24 to 1:9: the melt spinning temperature is 250 to 305°C, the spinning speed is 800 to 1500 m / min, the spinneret aperture is 0.2 to 0.5 mm, the stretching temperature is 60 to 120°C, and the stretching multiple is 3 to 4 times.
10. The long-lasting antibacterial polyamide fiber and its application as claimed in claim 1, characterized in that: The antibacterial polyamide fiber has a breaking strength of 3.5 to 5.8 cN / dtex, an elongation at break of 10% to 50%, and an antibacterial effect on Escherichia coli, Staphylococcus aureus, and Candida albicans of more than 99.99%. After the fiber is washed 50 times, the antibacterial effect on Escherichia coli, Staphylococcus aureus, and Candida albicans can still reach more than 99%. It has good washability and high-efficiency antibacterial properties, and can be used in the fields of home textile products such as clothing, protective clothing, bed sheets, socks, and carpets.
Citation Information
Patent Citations
Preparation method for nano copper oxide-loaded mesoporous zirconium phosphate antibacterial polyamide fiber
CN105332083A
Mesoporous zirconium phosphate-loaded nanosilver antibacterial polyamide fiber and preparation method thereof
CN105386147A
Color-change-resistant anti-bacterial polyamide fiber
CN108385202A
Preparation method of multi-amino modified nanometer zinc oxide-loaded polyamide fiber
CN111172609A
Preparation method of polyamide with temperature response negative ion release and antibacterial functions and fibers thereof
CN112430864A
Cited By
Antibacterial far infrared fiber and preparation method thereof
CN121610917A